A study of In vitro antifungal susceptibility patterns of dermatophytic fungi at a tertiary care center in Western India - Shital Poojary; Autar Miskeen; Jimish Bagadia; Saurabh Jaiswal; Priya Uppuluri (Wolters Kluwer Medknow Publications, 2019)
Background: Recent years have seen an alarming rise in the prevalence of recalcitrant and relapsing dermatophyte infections in India associated with lack of clinical response to standard antifungal regimens. Aims and Objectives: A study was undertaken to identify the antifungal susceptibility patterns of dermatophyte species isolated from lesions of dermatophytoses in patients examined at our center. Materials and Methods: A total of 85 patients with clinically diagnosed dermatophytoses were subjected to skin scrapings for potassium hydroxide mount (microscopic examination) and culture using Sabouraud's agar medium containing chloramphenicol and cycloheximide (incubated at 30°C). Antifungal susceptibilities [minimum inhibitory concentration-90 (MIC-90)] of the identified dermatophytes were tested for seven systemic and topical antifungal agents (terbinafine, griseofulvin, itraconazole, fluconazole, sertaconazole, ketoconazole, and clotrimazole) using Clinical and Laboratory Standards Institute broth microdilution method (M38-A). Results: Trichophyton rubrum (50%) and Trichophyton mentagrophytes complex (47.2%) were the two major species isolated. Isolates of both showed downy and granular forms (61.11%, 38.89% and 32.35%, 67.65%, respectively). The overall in-vitro susceptibility profiles (MIC-90 ranges in μg/mL) of the seven drugs for T. rubrum and T. mentagrophytes complex respectively were as follows: terbinafine (0.008-0256, 0.016-0.256), griseofulvin (0.03-1, 0.06-1), itraconazole (0.125-2, 0.25-2), fluconazole (0.125-1, 0.25-32), sertaconazole (0.03-1, 0.03-1), ketoconazole (0.06-1, 0.125-1), and clotrimazole (0.03-2, 0.06-1). Conclusions: This study indicates a rising proportion of T. mentagrophytes complex with increased proportion of granular form (T. mentagrophytes var. mentagrophytes). This study represents the current antifungal susceptibility profile of dermatophytic infections in a tertiary care medical center in western India with rising MICs to terbinafine and itraconazole.